THE ROLE OF BELONGINGNESS FOR CABIN CREW: BETWEEN WORK PASSION AND JOB SATISFACTION - Mantiri, Stephanie Maria; Sandroto, Christine Winstinindah (International Business Management - Universitas Ciputra, 2023)
Efforts to increase the job satisfaction of cabin crews must be a priority because their job satisfaction determines the services they provide to passengers throughout the flight. Factors that determine cabin crew job satisfaction include work passion and role of belongingness. This study examined the role of belongingness in the effect of work passion on the job satisfaction of cabin crews. The sample population was cabin crew in the Jakarta area who worked for various airlines. The sample was 70 respondents. The sampling technique used was non-probability sampling, with the convenience sampling method. This study performed validity and reliability tests; p plots normality tests, descriptive statistics, and Preacher Hayes analysis. The analysis method used The Simple Mediation Model, processed through SPSS Process 23.00. The results show that work passion positively affects both the role of belongingness and job satisfaction, and the role of belongingness positively affects job satisfaction. Job satisfaction is affected by the passion for work with the mediating variable role of belongingness. In conclusion, the role of belongingness has been proven to mediate the effect of work passion on job satisfaction for cabin crews in Jakarta.